2021
DOI: 10.3390/biomedicines9050513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidized Low-Density Lipoprotein on Head and Neck Squamous Cell Carcinomas

Abstract: Cardiovascular disease (CVD) and cancer are two major causes of death worldwide. The question is, “Could there be a link between these two pathologies in addition to their shared, common risk factors?” To find some answers, we studied the effect of oxidized low-density lipoproteins (oxLDL) on head and neck cancer (HNC) cell lines, since oxLDL is a major contributor to atherosclerosis and the principal cause of CVD. In this study, we exposed three HNC cell lines (Detroit 562, UPCI-SCC-131 and FaDu) to oxLDL. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The results obtained in this work on HPV-positive HNCC are in line with our previous results, obtained with reference to oxLDL [ 15 ] on HPV-negative HNCC (Detroit 562, UPCI-SCC-131 and FaDu), that indicated similar scavenger receptors expression and migration profiles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained in this work on HPV-positive HNCC are in line with our previous results, obtained with reference to oxLDL [ 15 ] on HPV-negative HNCC (Detroit 562, UPCI-SCC-131 and FaDu), that indicated similar scavenger receptors expression and migration profiles.…”
Section: Discussionsupporting
confidence: 91%
“…Our team recently studied the migration profile of head and neck cancer cells (HNCC) with Human Papilloma Virus (HPV) negative status, after exposure to commercial oxLDL. We demonstrated an increased expression of LOX-1 and CD36 receptors in HNCC after oxLDL exposure, and a decrease in cell migration via changes in the CD36/b-catenin pathway [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Daker et al also found that Epstein-Barr virus encoded RNA (EBERs) up-regulated LDLR and FA synthase (FASN) in NPC cells (35). Besides, experiments on head and neck cancer (HNC) cell lines revealed that the expression of CD36 and LOX-1, another two LDL membrane receptors, were significantly upregulated after exposure to oxidized LDL (oxLDL) (36), which also suggested that the uptake of cholesterol increased in HNSCCSs. However, lipid metabolism varies according to different tumor microenvironment (TME) and progression stages (37,38).…”
Section: Cholesterol Uptakementioning
confidence: 99%
“…However, lipid metabolism varies according to different tumor microenvironment (TME) and progression stages (37,38). When oxLDL upregulated CD36 in HNC cell lines, the migration of cancer cells were reduced after oxLDL exposure (36). Thus, the regulation of LDL receptors needs further exploration in order to guide the administration of cholesterol uptake inhibitor.…”
Section: Cholesterol Uptakementioning
confidence: 99%
“…An attempt was made to connect oxLDL with cancer as a risk factor. In the research paper devoted to the study of oxLDLs and their effects on head and neck cancer cell lines, it was found that the addition of oxLDL increased CD36 expression, leading to an increased lipid uptake and reduced cell migration [ 4 ].…”
mentioning
confidence: 99%